Al-Ghazali’s Thought on Creative Thinking - Darojat, Much Hasan; Yenrizal, Yenrizal; Izfanna, Duna (Tasfiyah: Jurnal Pemikiran Islam, 2024)
This article aims to discuss the model of creativity initiated by al-Ghazali. His contribution on creative thinking seems relevant to be studied as an answer to the problem of cheese and stagnant thinking to solve various problems. Creativity that boils down to the ability of reason is not just a creation to seek something new, but there is a divine element emitted to the human mind. Therefore, in facing the problems of the Ummah that arise, creative solutions are needed that are in line with Islamic teachings. However, what happens in society most problems cannot be resolved and even tend to end in conflicts and conflicts between groups. In presenting this concept, al-Ghazali analyzed al-AsmÄâ€™ al-á¸¤usnÄs theological terms such as al-KhÄliq, al-BÄriâ€™, al-Muá¹£awwir, al-BadÄ«â€™. Then relate to other aspects with the power of the internal senses such as common sense, thinking, imagination, estimation, and memory. This article is a literature review that applies qualitative methods through content analysis to express what is written in al-Ghazaliâ€™s works. Two findings in this study. First, al-Ghazaliâ€™s concept of creativity is principled from al-AsmÄâ€™ al-á¸¤usnÄ which is implemented by humans in everyday life by following what is exemplified by Allah, the Almighty, in His attributes. Manâ€™s potential to think creatively follows Godâ€™s creativity in creating His creatures. Second, human creativity can be seen from the role and results of the relationship between the five senses and the internal senses of a human being which continues to be developed in daily activities. These two senses work together to show humans the process of how to perceive the surrounding reality and then create to develop it. This implies sincerity in utilizing creativity in thinking to provide solutions to mankind to various problems in life.